The mirror for magistrates, 1559-1610: transmission, appropriation and the poetics of historiography - Archer, H (2012)
The Mirror for Magistrates, the collection of de casibus complaint poems compiled by William Baldwin in the 1550s and expanded and revised between 1559 and 1610, was central to the development of imaginative literature in the sixteenth and early seventeenth century. Additions by John Higgins, Thomas Blenerhasset and Richard Niccols extended the Mirror’s scope, shifted its focus, and prolonged its popularity; in particular, the 1587 edition of the original text with Higgins’s ancient British and Roman complaint collections profoundly influenced the work of Spenser and Shakespeare. However, while there has been a recent resurgence of critical interest in the editions of 1559 and its 1563 ‘Second Part’, the later additions are still largely neglected and disparaged, and the transmission of the original text beyond 1563 has never been fully explored. Without an understanding of this transmission and expansion, the importance of the Mirror to sixteenth-century intellectual culture is dramatically distorted. Higgins, Blenerhasset and Niccols’s contributions are invaluable witnesses to how verse history was conceptualised, written and read across the period, and to the way in which the Mirror tradition was repeatedly reinterpreted and redeployed in response to changing contemporary concerns. The Mirror corpus encompasses topical allegory, nationalist polemic, and historiographical scepticism. What has not been recognised is the complex interaction of these themes right across the Mirror’s history. This thesis provides a comprehensive reassessment of the Mirror’s expansion, transmission, and appropriation between 1559 and 1610, focusing in particular on Higgins, Blenerhasset, and Niccols’s work. By comparing editions and tracing editorial revisions, the changing contexts and attitudes which shaped the early texts’ development are explored. Higgins, Blenerhasset, and Niccols’s contributions are analysed against this backdrop for the first time here, both within their own literary and historiographical contexts, and in dialogue with the early editions. A broad reading of the themes and concerns of these recensions, rather than the limited approach which has characterised previous scholarship, takes account of their depth and variety, and provides a new understanding of the extent of the Mirror’s influence and ubiquity in early modern literary culture.